The challenges and countermeasures of MOOC to the teaching reform in universities - Jin, Yongxian; Jin, Mengqi (IJRDO- Journal of Educational Research, 2018)
As an emerging curriculum model, MOOC (Massive Open Online Course) has a grea impact on traditional university teaching by providing free teaching resources, realizing complete learning experience, and timely interaction to students.Through the overview of MOOC, this paper analyze many challenges to the reform of university teaching that MOOC brings. On this basis, it puts forward the strategies that should be taken in the teaching reform in universitie